Processes of Harmonization of the Eurasian Economic Community Member States’ Laws on Freedom of Conscience - Smorgunova, Valentina Yu; Dorskaia, Ðleksandra Ð.; Malysheva, Nataliya I.; Orlova, Inna A.; Pashentsev, Dmitriy Ð. (International Journal of Economics and Financial Issues, 2015)
The article discusses possible ways of harmonizing the Eurasian Economic Community member states’ legislation on the freedom of conscience. It is shown that the basis of harmonization is common approach developed over the centuries in existence within a single state – The Russian Empire and the Soviet Union, the legal documents of the Commonwealth of Independent States, the transfer of basic research from determining the signs of the secular state on to the development of individualistic and collective freedom of conscience. The current Law on Freedom of Conscience in Armenia, Belarus, Kazakhstan, Kyrgyzstan and the Russian Federation is analyzed. Keywords: Eurasian Economic Community, Freedom of Conscience, The Secular State, Church-State Relations, Religious Organizations JEL Classifications: F5, H7, K2